PENERAPAN METODE TUTOR SEBAYA PADA PEMBELAJARAN SENI MUSIK DI SMAN 4 MUARA BUNGO - Sri Wahyuni; Tulus Handra Kadir; Jagar Lumban Toruan (FBS Universitas Negeri Padang, 2013)
Abstract The aim of this research was to reveal the implementation of peer-tutoring method in arts and Music learning process at SMAN 4 Muara Bungo. This was an applied research in which in this research the research the researcher applied per-tutoring method by using qualitative method. This method was suited to the learning materials of the semester. The result of the research indicated that the application of peer-tutoring method in Rangkayo Hitam song especially those related to legato, cengkok, and vibration technique could improve the students’ learning achievement. The improvement could be seen from their average score which was above the minimum standard score (SKM) 71. Kata kunci: Siswa, kemandirian, tutor sebaya, bernyanyi, hasil belajar